Morphometric vertebral fracture risk in women with postsurgical hypoparathyroidism - d’Alva, Catarina Brasil; Barreto, André Rodrigues Façanha; Nogueira-Barbosa, Marcello H.; Arruda, Caio César Cavalcante; Albuquerque, Áurea Maíla; Praciano, Débora Mota Cordeiro; Viana, Rodrigo Ponte; Gadelha, Daniel Duarte; Viana Jr, Antônio Brazil; Moreira, Ilana Marques; Moura Filho, Francisco José Rodrigues de; Junqueira, Ana Flávia Torquato de Araújo; et al. (Frontiers in Endocrinology, 2022)
Introduction: Hypoparathyroidism (HP) is a rare endocrine disease and there are little data available on the risk of fragility fractures in these patients. PTH deficiency results in a positive bone balance with higher bone mass in all skeletal sites. However, whether these structural and dynamic skeletal changes have a negative impact on the fracture risk, it is not known. Methods: Aiming to investigate the risk of insufficiency vertebral fractures in HP, defined using morphometric criteria, a consecutive sampling of 44 women with chronic postsurgical HP was compared to a control group of 44 adult healthy women, matched by age with patients. Vertebral fractures were analyzed by the semiquantitative Genant’s method followed by quantitative vertebral morphometry. Results: Morphometric vertebral fractures were identified in 5/44 (11.4%) patients and in 3/44 (6.8%) controls (p=0.731). Most fractures were classified as Genant II and III grades in HP patients, whereas most were Genant I in controls. A logistic regression multivariate analysis was conducted in which age, BMI and parathyroid status were the independent variables, and morphometric vertebral fracture was the dependent variable, but none of these factors was a significant predictor of fracture in this population (OR 1.01, 95% CI 0.96-1.07, p=0.634 for age; OR 2.24, 95%CI 0.47-10.50, p=0.306 for the presence/absence of HP and OR 0.92, 95% CI 0.76-1.10, p=0.369 for BMI). Conclusion: The results of this study cannot ensure a higher risk of fragility vertebral fractures in postsurgical HP patients. Instead, we only observed higher Genant grade classification of the deformed vertebrae in our sample.